2011
DOI: 10.3109/01443615.2011.578776
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transobturator tape (TOT) vs Burch method in treatment of stress urinary incontinence

Abstract: This study aim was to compare the efficacy of transobturator tape (TOT) as a new sling procedure, and Burch colposuspension as the gold standard surgical technique, in the treatment of stress urinary incontinence (SUI). This prospective randomised clinical trial was conducted on 62 women with SUI diagnosed with urodynamic test in Vali-e-Asr Hospital, Tehran, Iran. Patients were allocated into two surgery groups, randomly; TOT and Burch (31 patients in each group). After treatment, they were followed-up for lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
2
19
0
1
Order By: Relevance
“…In our study, TOT was found more superior over Burch operation in providing SUI. Although there are some studies supporting the results of our study in the literature (21,22), a study showed that Burch colposuspension surgery is more successful than TOT operation (23).…”
Section: Discussionsupporting
confidence: 36%
“…In our study, TOT was found more superior over Burch operation in providing SUI. Although there are some studies supporting the results of our study in the literature (21,22), a study showed that Burch colposuspension surgery is more successful than TOT operation (23).…”
Section: Discussionsupporting
confidence: 36%
“…In presence of positive MT with CRM, a clear explanation should be given to the patient for avoiding an unpleasant postoperative surprise. As a confirmation of these, our statement is the fact that this percent, which we found as positive MT during CRP, is similar to those reported by most authors as a failure rate after anti-stress surgery [10, 19]. The noted percentage of positive MT during CRM in patients with isolated USI gave an affirmation of our second hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the different antistress procedures in patients with USI without GP also can result in postoperative failure, perhaps due to vertical pelvic organ position. Different authors report different failure rate, from more than 30% to less than 10% [1012]. Nevertheless, the cure rate shows a decreasing trend over the time.…”
Section: Introductionmentioning
confidence: 99%
“…38 The same review confirmed results from two older randomized controlled trials including assessment of both the retropubic and transobturator MUS placement. 47,48 In a nationwide cohort study, Foss Hansen and colleagues reported, that Burch colposuspension MUS had a similar risk of reoperation (6%). 49 Another study conducted by Holdø and colleagues showed a significantly lower cumulative rate of recurrence up to 12 years after retropubic MUS than after Burch colposuspension.…”
Section: Open Burch Colposuspension and Midurethral Slingsmentioning
confidence: 98%